Repatriation of Polish refugees of World War I: the case of the Altai Province - Yurii M. Goncharov (Peoples’ Friendship University of Russia (RUDN University), 2021)
During World War I a large number of refugees evacuated to the Russian Empires periphery, such as the many Poles who were temporarily transported eastward to Siberia. This article studies their repatriation after the conflicts end, which bears some relevance to forced migration, refugees and repatriation in todays world. Based on archival and secondary sources, the authors endeavor to reconstruct the repatriation of Polish refugees from Altai province in southern Siberia. Beginning in earnest after the Soviet Unions war with Poland of 1918-21, their return was hampered by the difficult conditions of the past Civil War and the countrys economic crisis. Although an extensive network of organizations was set up to carry the repatriation out, poor communication with the center, insufficient staff and the absence of registration forms made its work extremely difficult. At the same time, many refugees returned on their own, which further complicated matters. Nevertheless, most Poles eventually made it back home. The Russian-Ukrainian-Polish Mixed Commission on Repatriation announced that its work was done in 1924, although in fact it lasted for another year.